3. DYSEMBRYOPLASTIC NEUROEPITHELIAL TUMOUR-LIKE NEOPLASM OF THE SEPTUM PELLUCIDUM: A CASE REPORT. (February 2015) - Allanson, B. M.; Thomas, A.; Lind, C.; Robbins, P.
Abstract : Background: Dysembryoplastic Neuroepithelial Tumour-like Neoplasm of the Septum Pellucidum is a rare, low grade CNS neoplasm that may be misdiagnosed as a diffuse glioma. Clinical features: We report a case of a 22 year old woman who presented with a first seizure. She was found to have a 31 mm non-enhancing cystic lesion on the right hand side of the anterior septum pellucidum. Pathological features: The lesion was completely resected and the specimen was received as fragmented pale-white gelatinous pieces of tissue. Histologically the lesion demonstrated a lobular, microcystic, and mucin-rich appearance, and had relatively well defined margins. A population of small uniform cells, often with perinuclear halos, and cytologically virtually indistinguishable from oligodendroglioma predominated. These small 'oligodendrocyte-like cells' (OLC) formed somewhat 'patterned' architectural arrangements with perivascular pseudorosettes and laminated arrays resembling the specific glioneuronal component of a dysembryoplastic neuroepithelial tumour. Rare individual neurons 'floating' in myxoid microcystic spaces were also present. These floating neurons lacked dysplastic features and evidence of satellitosis. Immunohistochemical staining showed mixed glioneuronal differentiation and the MIB1 proliferation index was low (less than 1%). PCR amplification and Sanger direct bidirectional sequencing for IDH1 and IDH2 mutations were negative. Discussion: Less than 20 cases of this rare tumour have been reported to date. DNT-like lesions should be included in differential diagnosis of midline intraventricular tumours in children and young adults. Distinction from diffuse glioma is essential because these tumours appear to behave in a benign fashion.